Penggunaan Media Kartu Kata untuk Meningkatkan Kemampuan Membaca Permulaan pada Siswa Kelas I Sekolah Dasar - Valentina Sani, Feby Resti; Widjojoko, Widjojoko; Wardana, Deni (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This study aims to see the potential to improve elementary school students' reading skills using word cards as media. This literature study research was conducted on research sources from undergraduate thesis and scientific journals. Based on the results of the analysis of literature studies that have been conducted by researchers, the results obtained by the previous researchers explained that the interaction activities of learners with teachers when the process of reading the beginning using the media card is done with 4 stages starting from the planning, action, observation, and reflection stages. The results of the increase in mastery of early reading by utilizing the medium of word cards, beginning with the previous researchers with pre-activity obtained an average percentage of 59.2%, results obtained with an average of 68.8% obtained cycle I, obtained an average of 75.2% cycle II, and cycle III got an average result of 78%. Based on secondary data that researchers conducted in interviews, the source said the process of reading the beginning using the word card media can improve students' initial reading ability compared to the conventional way before and can make students active in the classroom because they are involved during the learning process. This can show that the process of early reading learning activities with word card media can improve the reading ability of grade 1 elementary school students.